Preparation of activated carbon from fruit of Wodyetia bifurcate A.K irvine - Nur Sabiha Sairan (2015)
Urbanization and rapid industrialization in Malaysia has become the major source in the spreading of pollution contaminants. Human activities such as mining, smelting. agricultural activities and others were making the condition even worst. The contaminants which needs warrant disposal was directly or indirectly disposed into water bodies. Hence, promoting the accumulation of heavy metals such as zinc ions (Zn) , lead ions (Pb) and ferum ions (Fe). Continuous researches were done to seek for the solution. Recently, a method called adsorption techniques was founded as the best treatment by utilizing the agricultural biomass. In this research, the activated carbon was obtained from wodyetia bifurcate I.K Irvine fruit or known as foxtail fruit. The activated carbon was activated by three different activating reagents. Potassium hydroxide, phosphoric acid and zinc chloride were used to determine their effectiveness upon treating the selected heavy metals. The removal percentage of Fe, Zn and Pb by activated carbon from foxtail fruit were also compared in this research. The result shows that activated carbon produced from zinc chloride and phosphoric acid activation has successfully adsorb Fe ions, activated carbon produced from phosphoric acid activation has successfully adsorb Pb ions while activated carbon produced from zinc chloride activation has successfully adsorb Zn ions in synthetic wastewater.